(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2026)
This article analyzes the performance Aparição Vomitada, carried out in Itaituba, (Pará), as a research-creation project situated in the urban Amazon. Drawing on a critique of the discourse that normalizes gold mining in the so-called “gold town”, the text articulates a description of the work, process memory, and critical reflection following the realization of the action in order to examine how the metaphorical gesture of vomiting, the occupation of the street, the use of banana fiber, and the relationship between performer and audience configure the body-territory as an insurgent practice in the face of the Capitalocene.